2019
DOI: 10.3892/ol.2019.10618
|View full text |Cite
|
Sign up to set email alerts
|

High expression of CD47 in triple negative breast cancer is associated with epithelial‑mesenchymal transition and poor prognosis

Abstract: CD47 functions as a dominant anti-engulfment signal on tumour cells and is overexpressed in various malignant tumours. However, the expression and functional significance of CD47 in triple-negative breast cancer (TNBC) is not completely understood. In the present study, CD47 was demonstrated to be overexpressed in TNBC solid tumours. Moreover, increased CD47 expression was significantly associated with an advanced tumour-node-metastasis stage, lymph node involvement and recurrence. Moreover, CD47 was an unfavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 39 publications
3
66
0
1
Order By: Relevance
“…As for ZC3H18 (Zinc finger CCCH domain-containing protein 18), our study suggested that the gene of ZC3H18 could be regarded as a protective factor and negatively associated with CD47 ( Figure 9C). Massive studies have shown that overexpression of CD47 predicts poor prognosis and promotes cancer cell invasion in many types of cancer [32][33][34]. What is more, in this correlation network, we found most of alternative splicing events were associated with poor overall survival and positively co-related to splicing factors.…”
Section: Discussionsupporting
confidence: 56%
“…As for ZC3H18 (Zinc finger CCCH domain-containing protein 18), our study suggested that the gene of ZC3H18 could be regarded as a protective factor and negatively associated with CD47 ( Figure 9C). Massive studies have shown that overexpression of CD47 predicts poor prognosis and promotes cancer cell invasion in many types of cancer [32][33][34]. What is more, in this correlation network, we found most of alternative splicing events were associated with poor overall survival and positively co-related to splicing factors.…”
Section: Discussionsupporting
confidence: 56%
“…14 However, recent studies revealed that CD47, which was associated with several clinicopathological characteristics, was not an independent predictor of poor DFS in breast cancer. 10,11 The inconsistency across different studies may be due to variations in immunohistochemical techniques and differences between the cancers, including type, stage, and treatment history. We consider that CD47 is a feasible prognostic biomarker of NPC patients.…”
Section: Discussionmentioning
confidence: 99%
“…9 Several studies have demonstrated that high CD47 expression predicts poor prognosis in several cancers. [10][11][12][13][14] However, little is known about the expression and role of CD47 in NPC.…”
Section: Introductionmentioning
confidence: 99%
“…By binding to signal regulatory protein α (SIRPα), among others expressed by neutrophils, it inhibits phagocytic uptake or trogocytosis ( Figure 4 B; panel 1). Cancer cells hijack this inhibitory CD47–SIRPα pathway by overexpressing CD47, which is associated with poor prognosis in both solid [ 184 , 185 ] and hematological cancers [ 3 , 186 ]. Furthermore, significantly lower CD47 expression levels were detected on breast cancer cells of human patients that responded with a complete response after trastuzumab plus vinorelbine therapy [ 187 ].…”
Section: Fcr-mediated Neutrophil Activation; Targeting Fcγriia (Cdmentioning
confidence: 99%